Development of an IoT Temperature Fish Hold Monitoring System for Cooling Crab Fish Based on Hybrid Ice-Peltier with a Modified Finned Boiling Pot - Wahab, Aulia Azhar; Iskandar, Budi Hascaryo; Yopi, Novita; Kurniawati, Vita Rumanti; Uju, Uju (Engineering, Technology & Applied Science Research, 2026)
Small-scale blue swimming crab fishing vessels (<5 gross tonnage) commonly rely on conventional ice-based storage systems with limited temperature control and monitoring during onboard handling. This study presents an integrated onboard handling system that combines fishing vessel design analysis, a hybrid ice–thermoelectric (Peltier-based) smart fish hold, Internet of Things (IoT)-based real-time temperature monitoring, and a modified crab boiling pot equipped with damping fins. The vessel’s general arrangement, hull form, and fineness coefficients were analyzed to assess their suitability for onboard boiling, handling, and storage activities. The smart fish hold was designed using ice as the primary cooling medium and supported by a thermoelectric module to stabilize the storage temperature. Temperature conditions inside the hold were continuously monitored using an IoT-based system with real-time alerts. In addition, damping fins were applied to the boiling pot to mitigate sloshing effects during vessel motion. The results indicate that the hybrid cooling system successfully maintained storage temperatures at approximately 4 °C, thereby supporting onboard cold chain requirements, while the monitoring system enabled continuous observation of thermal conditions. Overall, the proposed system demonstrates a practical engineering solution for improving onboard quality management and operational safety on small-scale crab fishing vessels.